el-Ürdün min hilâl vesâiki’l-arşîfi’l-Osmânî (İstanbul : Amman)
719, [1] sayfa
Keywords: “...تحتل الوثائق المتعلقة بالأردن حيزاً مهماً ضمن مجموعات وثائق الأرشيف العثماني نظراً للموقع الذي يحتله الأردن ولمرور طريق الحج الشامي من دمشق إلى الحرمين عبر أراضيه وما شهدته منطقة الأردن من أحداث مختلفة طيلة العهد العثماني. وهذه الوثائق محفوظة في تصانيف مختلفة من هذا الأرشيف وصُنِّفت حسب ما كانت موجودة في الدوائر العثمانية المختلفة. وقام المُعِدُّ باستعراض المعلومات الواردة في الوثائق وتبويبها موضوعيا وترتيب كل موضوع من الناحية الزمنية، وسعى جاهدا إلى الإحاطة بحيثيات الموضوع الواحد بشكل متكامل وحسب وروده في الوثائق وتفريغ المعلومات الواردة فيها. ونظرا لاستحالة نشر كل الوثائق فقد اكتفى المؤلف في الكتاب بنشر 413 وثيقة قام بدراستها تحت عناوين الفصول الآتية: بداية توطيد الحكم العثماني في مناطق عجلون والكرك والشوبك ومعان؛ وعائلة قنصو بك الغزاوي: أمراء عجلون والكرك؛ وعهد الباشوات؛ والشؤون الإدارية؛ والشؤون البلدية والعمرانية والصحية والخدمات العامة؛ وشؤون التعليم والمؤسسات التعليمية؛ والمؤسسات التعليمية المسيحية والتبشيرية؛ والشؤون القضائية؛ والمؤسسات والأوقاف والشؤون الدينية الإسلامية؛ وشؤون الطوائف المسيحية؛ وشخصيات أردنية في الإدارة المحلية ومجلس المبعوثان العثماني؛ وتكريم وجهاء البلدات وشيوخ العشائر؛ وإسكان المهاجرين. والقسم الأكبر من الوثائق المنشورة في الكتاب عبارة عن وثائق مفردة معظمها كُتب رسمية، وقسم منها ورد مسجلاً في الدفاتر/ السجلات. كما يتضمن الكتاب خارطتين و23 صورة فوتوغرافية تاريخية عن الأردن التقطت في أوائل القرن العشرين. تبرز الوثائق جوانب مخفية من تاريخ الأردن وتكشف الكثير من الغموض الذي يكتنفه، ولهذا فهي مصادر أساسية لكل من يتناول هذه الحقبة المدروسة“ -- “...Documents relating to Jordan hold an important place in the collections of the Ottoman Archives due to the historical significance of Jordan located on the pilgrimage routes that cross Bilad al-Sham from Damascus to the Haramayn and on account of the various events the region witnessed throughout the Ottoman era. These documents are classified in the Ottoman Archives system under the same designations they were assigned by the Ottoman State departments. In the book, the author grouped them under chronologically ordered subject headings and gave information on their contents, delving into the background and general historical context of each subject treated in the documents. Given the impossibility of publishing whole collections of documents, the author limited the book to 413 documents that he examined under the following chapter headings: The Early Rise of Ottoman Rule in the Regions of Ajlun, Karak, Shubak and Maʿan; Qansuh Bey Al-Ghazzawi Family: The Emirs of Ajlun and Karak; The Rule of Pashas; Administrative Affairs; Municipal, Urban, Public Health and Public Services Affairs; Education and Teaching Establishments; Christian Missionary Educational Institutions; Judicial Affairs; Islamic Institutions, Waqfs and Religious Affairs; Matters Relating to Christian Communities; Jordanian Personalities in the Local Administrations and the Ottoman Chamber of Deputies (Meclis-i Mebusan); Tributes Paid to City Notables and Chieftains; Accommodation of İmmigrants. The majority of the documents published in the book consist of sheets, most of them official letters, some of them comprised in the Registers (Defter). The book also contains two geographical maps and 23 historical photographs of Jordan from early 20th century. The documents presented in the book clarify many unknown aspects of the history of Jordan and demystify some facts surrounding this history. Therefore, they are essential sources for anyone interested in the history of Jordan during the period under focus“ -- “...Bilad-ı Şam üzerinden Haremeyn’e ulaşan Hac yolları üzerinde bulunan ve Osmanlı tarihinin birçok hadisesine şahit olan Ürdün ile ilgili belgeler Osmanlı Arşivi koleksiyonlarında önemli bir yer tutmaktadır. Bu belgelerin arşivdeki sınıflandırması Osmanlı Devlet idaresinin sınıflandırmasındaki başlıklara göre uygulanmıştır. Yazar kitapta bunları konularına göre gruplandırmış, konuları ise kronolojik olarak dizmiştir. Muhtevaları hakkında açıklamalar verirken belgelerdeki her konunun tarihî temeline ve bağlamına inmiştir. Tüm belge koleksiyonlarını yayınlamanın imkansızlığını göz önüne alarak kitapta 413 belge kapsamış, bunları şu başlıklar altında incelemiştir: Aclun, Karak, Şubak ve Maan bölgelerinde Osmanlı idaresinin güçlenmesinin başlangıç dönemi; Kansu Gazavî ailesi; Aclun ve Karak Emirleri; Paşalar yönetimi; İdarî meseleler; Belediye, şehir, sağlık ve kamu hizmetleri meseleleri; Eğitim ve öğretim kurumları; Hıristiyan misyonerlerin eğitim kurumları; Hukukî meseleler; İslamî kurumlar, vakıflar ve din işleri; Hıristiyan milletlere dair meseleler; Yerel yönetimlerde ve Osmanlı Meclis-i Mebusanında Ürdünlü şahsiyetler; Şehir eşrafına ve aile reislerine verilen imtiyazlar; Göçmenlerin yerleştirilmesi. Kitapta yayınlanan belgelerin büyük kısmı tek varaktan oluşan, çoğunluğu arşivdeki defterlere dahil resmî mektuplardır. Kitapta iki coğrafî harita ve 20. asır başında çekilmiş 23 Ürdün fotoğrafı bulunmaktadır. Kitaptaki belgeler Ürdün tarihinin saklı kalmış birçok yönüne ışık tutmakta, bilinmeyen olayları açıklığa kavuşturmaktadır. Bu bakımdan, Ürdün tarihinin söz konusu dönemiyle ilgilenen herkes için temel kaynaklardır“ --